In vitro antimicrobial, physicochemical, pharmacokinetics and molecular docking studies of benzoyl uridine esters against SARS-CoV-2 main protease - Matin, Mohammed Mahbubul (J Biomol Struct Dyn, 2020)
Different esters were found potential against microorganisms, and could be a better choice to solve the multidrug resistant (MDR) pathogenic global issue due to their improved biological and pharmacokinetic properties. In this view, several 4-t-butylbenzoyl uridine esters 4–15 with different aliphatic and aromatic groups were synthesized for antimicrobial, physicochemical and biological studies. In vitro antimicrobial tests against nine bacteria and three fungi along with prediction of activity spectra for substances (PASS) indicated promising antifungal functionality of these uridine esters compared to the antibacterial activities. In support of this observation their cytotoxicity and molecular docking studies have been performed against lanosterol 14α-demethylase (CYP51A1) and Aspergillus flavus (1R51). Significant binding affinities were observed against SARS-CoV-2 main protease (7BQY) considering hydroxychloroquine (HCQ) as standard. ADMET predictions were investigated to evaluate their absorption, metabolism and toxic properties. Most of the uridine esters showed better results than that of the HCQ. Overall, the present study might be useful for the development of uridine-based novel MDR antimicrobial and COVID-19 drugs.